HIV protease inhibitor ritonavir: a more potent inhibitor of P-glycoprotein than the cyclosporine analog SDZ PSC 833 - Drewe, Jürgen; Gutmann, Heike; Fricker, Gert; Török, Michael; Beglinger, Christoph; Huwyler, Jörg (Biochemical pharmacology, 1999)
The effect of P-glycoprotein inhibition on the uptake of the HIV type 1 protease inhibitor saquinavir into brain capillary endothelial cells was studied using porcine primary brain capillary endothelial cell monolayers as an in vitro test system. As confirmed by polymerase chain reaction and Western blot analysis, this system functionally expressed class I P-glycoprotein (pgp1A). P-Glycoprotein isoforms pgp1B or pgp1D could not be detected. The uptake of saquinavir into endothelial cells could be described as the result of a diffusional term of uptake and an oppositely directed saturable extrusion process. Net uptake of saquinavir into cultured brain endothelial cells could be increased significantly up to 2-fold by SDZ PSC 833 in a dose-dependent manner, with an ic50 of 1.13 μM. In addition, the HIV protease inhibitor ritonavir inhibited p-glycoprotein-mediated extrusion of saquinavir with an ic50 of 0.2 μM, indicating a high affinity of ritonavir for p-glycoprotein. In conclusion, we showed that the HIV protease inhibitor ritonavir is a more potent inhibitor of P-glycoprotein than the multidrug resistance (MDR)-reversing agent SDZ PSC 833. The inclusion of this drug in combination regimens may greatly facilitate brain uptake of HIV protease inhibitors, which is especially important in patients suffering from AIDS dementia complex.
Gesehen am 26.04.2017